Meningkatkan Produktivitas Melalui Keterlibatan Karyawan: Tinjauan dalam Manajemen Sumber Daya Manusia - Siti Jumaidah; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Employee engagement is an important factor in increasing productivity in the workplace. This study aims to analyze the relationship between employee engagement and productivity, and identify the elements that influence the level of engagement. Using a qualitative approach through literature study and document analysis from various organizations, this study explores best practices in human resource management that support employee engagement. The findings indicate that factors such as effective communication, recognition of achievements, and opportunities to participate in decision-making play a significant role in increasing engagement. In addition, an inclusive work environment and a positive organizational culture contribute to increasing employee motivation and commitment.